A hybrid Input-Output multi-objective model to assess economic-energy-environment trade-offs: an application to Brazil and prospective sugarcane bioethanol technologies - Carvalho, Ariovaldo Lopes de (2016)
Tese de doutoramento em Sistemas de Energia Sustentável, apresentada ao Departamento de Engenharia Mecânica da Faculdade de Ciências e Tecnologia da Universidade de Coimbra